Posibles alteraciones en el sustrato neurobiológico y conductual provocadas por la separación materna temprana en un modelo de depresión : tratamiento con tianeptina - Pollano, Antonella Universidad Nacional de Córdoba. Facultad de Ciencias Químicas ([s. n.], 2018)
Vulnerability to emotional disorders like depression derives from interactions between early and late environments, includ ing stressfu 1 cond ¡tions. Early maternal separation produces lasting neurobiological effects that can change the response to chronic stress during adulthood. Chronic stress strongly affects the serotonergic system, and produces dendritic retraction modifying the morphology of the dorsal hippocampus. Contextual memory depends on this structure, but the antidepressant thianeptine reverses those morphological modifications induced by stress. Therefore, we evaluated whether, the interaction between early maternal separation and chronic stress affects 1) the distribution of active serotonergic neurons in the dorsal raphe nucleus (DAN) through immunohistochemistry, 2) the volume of the dorsal hippocampus and its areas using stereology and 3) the hippocampal-dependent memory using a contextual fear conditioning parad igm, in rats treated with tianeptine. Male Wistar rats were subjected to daily maternal separation for 4.5 h between postnatal days (PND) 1- 21. Between PND days 50-74, rats were exposed to chronic unpredictable stress and simultaneously treated with tianeptine (10 mg/kg), providing eight groups: unstressed/vehicle, unstressed/tianeptine, chronic stress/vehicle chronic stress/tianeptine, maternal separation -unstressed/vehicle, maternal separation-unstressed/tianeptine maternal separation-chronic stress/vehicle and maternal separationchronic stress/tianeptine. We found an interaction between the effects of maternal separation and unpredictable chronic stress on the number of 5HT active neurons of the DAN and contextual memory. The combination of these stressors produced an increase in the activation of 5HT celis compared to rats only subjected to chronic stress, reaching the same value as the controls. Similarly, when both stressors were applied, the memory of fear to the context was similar to controls, while each stress protocol separately reduced the recall of this memory. The antidepressant thianeptine produced a decrease in the volume of the dorsal hippocampus in the separated and stressed rats, compared to those only subjected to maternal separation. When the two stressors combine, both the activation levels of 5HT neurons in the DAN and the contextual memory are similar to controls. Consequently, our date support the idea of a match in phenotype exhibited when the early and the adult environment correspond.